Generasi Digital Sejak Lahir: Perspektif Sosiologi Digital pada Gen Alpha - Aini Nurpratiwi; Syawal Akhir; Riswandy Marsuki (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Generation Alpha, born between 2010 and 2025, is immersed in a digital era that shapes their social, cultural, and educational experiences. This study examines the sociological implications of technology on their identity formation and the adaptations required in their education and parenting. Through literature analysis, findings reveal that Generation Alpha is highly dependent on technology, which affects their communication and social interactions. While technology increases access to knowledge, it also poses risks such as social isolation and shifting cultural values. This study underlines the importance of collaboration between families, educational institutions, and communities to foster holistic development, addressing the challenges of globalization and technological advancement.